Why Parents Misuse Prescription Drugs to Enhance the Cognitive Performance of Healthy Children: the Influence of Peers and Social Media - Sattler, Sebastian (Journal of drug issues)
The mechanisms affecting parents’ misuse of prescription stimulant drugs to boost healthy children’s school performance are hardly unknown. Using four web-based factorial vignette surveys (2×2 between-subjects design experiment), we investigated the willingness of U.S. parents with school-aged children to medicate a fictitious 13-year-old child whose grades had declined. We examined mechanisms of informational and normative social influence on their decision-making: others’ behavior (NExperiment 1 = 359), others’ definitions (NExperiment 2 = 326), social control (NExperiment 3 = 325), and others’ experience (NExperiment 4 = 313). In addition, we explored the moderating role of influential sources (close friends vs. social media). Parents were more willing to engage in said behavior when others reported engagement in this behavior or positive drug experiences, especially if both influences were transmitted via social media. Others’ definitions and social control had no effect. Thus, social media might be a channel for the prevention of pharmacological cognitive enhancement.